Acidosis slows electrical conduction through the atrio-ventricular node - Nisbet, Ashley M.; Burton, Francis L.; Walker, Nicola L.; Craig, Margaret A.; Cheng, Hongwei; Hancox, Jules C.; Orchard, Clive H.; Smith, Godfrey L. (Frontiers in Physiology, 2014)
Acidosis affects the mechanical and electrical activity of mammalian hearts but comparatively little is known about its effects on the function of the atrio-ventricular node (AVN). In this study, the electrical activity of the epicardial surface of the left ventricle of isolated Langendorff-perfused rabbit hearts was examined using optical methods. Perfusion with hypercapnic Tyrode’s solution (20% CO2, pH 6.7) increased the time of earliest activation (Tact) from 100.5+7.9 to 166.1+7.2ms (n=8) at a pacing cycle length (PCL) of 300ms (37oC). Tact increased at shorter PCL, and the hypercapnic solution prolonged Tact further: at 150ms PCL, Tact was prolonged from 131.0+5.2 to 174.9+16.3ms. 2:1 AVN block was common at shorter cycle lengths. Atrial and ventricular conduction times were not significantly affected by the hypercapnic solution suggesting that the increased delay originated in the AVN. Isolated right atrial preparations were superfused with Tyrode’s solutions at pH 7.4 (control), 6.8 and 6.3. Low pH prolonged the atrial-Hisian (AH) interval, the effective and functional refractory periods and Wenckebach cycle length significantly. Complete AVN block occurred in 6 out of 9 preparations. Optical imaging of conduction at the AV junction revealed increased conduction delay in the region of the AVN, with less marked effects in atrial and ventricular tissue. Thus acidosis can dramatically prolong the AVN delay, and in combination with short cycle lengths, this can cause partial or complete AVN block and is therefore implicated in the development of brady-arrhythmias in conditions of local or systemic acidosis.